2018
DOI: 10.1007/s12223-018-0643-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative restriction enzyme mapping of Campylobacter jejuni isolates from turkeys and broilers based on flaA flagellar gene using HpyF3I endonuclease

Abstract: Turkeys and broilers have been identified as important reservoirs for Campylobacter jejuni which is of public health significance. The evaluation of the genotypes among C. jejuni strains within different reservoirs is critical for our understanding of the epidemiology of this infectious agent. The present study aimed to compare the genetic diversity and differences of C. jejuni isolates from turkeys and broilers using flagellin PCR-RFLP typing (flaA typing) technique, in terms of the ease of use and discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Both RFLP and ARDRA require the use of endonucleases to digest specific PCR amplification products and then obtain fragments of different numbers and lengths to distinguish bacteria. This method is suitable for strains that have been successfully isolated and can determine whether there are differences in the genus of a large number of strains [ 90 , 91 ] ( Table 2 ). He et al identified 12 and 11 species in the Camponotus midgut, respectively, utilizing traditional culture methods and 16S rRNA-RFLP technology [ 92 ].…”
Section: Detection Methods Of Insect Gut Microbesmentioning
confidence: 99%
“…Both RFLP and ARDRA require the use of endonucleases to digest specific PCR amplification products and then obtain fragments of different numbers and lengths to distinguish bacteria. This method is suitable for strains that have been successfully isolated and can determine whether there are differences in the genus of a large number of strains [ 90 , 91 ] ( Table 2 ). He et al identified 12 and 11 species in the Camponotus midgut, respectively, utilizing traditional culture methods and 16S rRNA-RFLP technology [ 92 ].…”
Section: Detection Methods Of Insect Gut Microbesmentioning
confidence: 99%